LURC and First Principles of Land Use Regulation - Anderson, Mark (Maine Policy Review, 2007)
In this commentary, Mark W. Anderson notes that recognizing the strengths and limits inherent in what Maine’s Land Use Planning Commission (LURC) does can bring more realism to how various “publics” seek to accomplish their goals for the North Woods.